Analisis Kebijakan Pengelolaan Sampah Berdasarkan Peraturan Daerah (Perda) Kota Pangkalpinang Nomor 6 Tahun 2013 - Siti Ulfah; Darol Arkum; Firdaus Komar (PERSPEKTIF, 2026)
This study aims to analyze the implementation of waste management policies based on Pangkalpinang City Regional Regulation Number 6 of 2013 by using the policy implementation theory of Van Meter and Van Horn (1975) as an analytical framework. This study uses a descriptive qualitative approach that focuses on the policy implementation process by the Pangkalpinang City Environmental Agency (DLH). Data were collected through in-depth interviews, field observations, and documentation studies. The results of the study show that the implementation of the policy has been running, but it has not been optimal due to limited human resources, infrastructure, and the lack of operational standards for derivative procedures from the Regional Regulation. The main supporting factors include local government commitment, political support, and community participation through the waste bank program. Meanwhile, inhibiting factors include weak vertical coordination, lack of budget, and low public awareness of cleanliness. The research recommendations include institutional strengthening, capacity building of implementers, and the application of adaptive governance principles to realize participatory and sustainable waste management in Pangkalpinang City.